IMPLEMENTASI KEBIJAKAN PANGAN SEHAT DAN BEBAS BAHAN BERBAHAYA DI KOTA PAYAKUMBUH - Rifandra Akbari; Hasim As’ari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Before starting a business, business actors such as the Home Food Industry (HFI) must have dealt with administrative matters such as permits. The Payakumbuh City Government has also regulated this in the Payakumbuh City Regional Regulation Number 1 of 2014 concerning Healthy Food and Free of Hazardous Materials, it is stated